THE IMPACT OF HALAL LOGOS AND HALAL LOGOS OF COUNTRY OF ORIGIN (COO) ON THE PURCHASE OF PACKAGED FOOD FROM ABROAD IN LHOKSEUMAWE CITY - Rasyidusman Hannamara Furqan Nur; Ratnawati Ratnawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the influence of halal logos in Indonesia and halal logos issued from abroad/Halal Country of Origin (COO) such as those originating from Korea on consumers' decisions to purchase packaged products from Korea. This study employs a logistic regression model, also commonly known as the logit model. The data used are primary data with a total of 100 respondents. The results of this study also indicate that halal logos significantly influence purchasing decisions in the city of Lhokseumawe. However, the Halal logo Country of Origin (COO) is not significant in consumer purchasing decisions. The Halal logo also reflects good product quality, even equivalent to the Indonesian National Standard (SNI), and demonstrates concern for animal welfare. Based on the results of this study, companies can formulate policies to better reach both Muslim and non-Muslim markets for future business development.